Mirored mesage wall: Bridging the real and virtual comunity - Tan, B.-K. (2013)
Circuit Bending, Breaking and Mending - Proceedings of the 16th International Conference on Computer-Aided Architectural Design Research in Asia, CAADRIA 2011